Genetic diversity in Oryza glumaepatula wild rice populations in Costa Rica and possible gene flow from O. sativa - Fuchs Castillo, Eric J. (2016)
Wild crop relatives are an important source of genetic diversity for crop improvement. Diversity estimates are generally lacking for many wild crop relatives. The objective of the present study was to analyze how genetic diversity is distributed within and among populations of the wild rice species Oryza glumaepatula in Costa Rica. We also evaluated the likelihood of gene flow between wild and commercial rice species because the latter is commonly sympatric with wild rice populations. Introgression may change wild species by incorporating alleles from domesticated species, increasing the risk of losing original variation. Specimens from all known O. glumaepatula populations in Costa Rica were analyzed with 444 AFLP markers to characterize genetic diversity and structure. We also compared genetic diversity estimates between O. glumaepatula specimens and O. sativa commercial rice. Our results showed that O. glumaepatula populations in Costa Rica have moderately high levels of genetic diversity, comparable to those found in South American populations. Despite the restricted distribution of this species in Costa Rica, populations are fairly large, reducing the effects of drift on genetic diversity. We found a dismissible but significant structure (θ = 0.02 ± 0.001) among populations. A Bayesian structure analysis suggested that some individuals share a significant proportion of their genomes with O. sativa. These results suggest that gene flow from cultivated O. sativa populations may have occurred in the recent past. These results expose an important biohazard: recurrent hybridization may reduce the genetic diversity of this wild rice species. Introgression may transfer commercial traits into O. glumaepatula, which in turn could alter genetic diversity and increase the likelihood of local extinction. These results have important implications for in situ conservation strategies of the only wild populations of O. glumaepatula in Costa Rica.